PERBANDINGAN EFEKTIFITAS OBAT ANTIHIPERTENSI ORAL ANTARA CANDESARTAN DAN VALSARTAN PADA PASIEN RAWAT JALAN DI RUMAH SAKIT ISLAM SULTAN AGUNG SEMARANG - Timur, Willi Wahyu; Mufadillah, Isna Naili; Mardiyanti, Devi (JFM (Jurnal Farmasi Malahayati), 2025)
Hypertension is a non-communicable disease that is responsible for 72% of deaths worldwide. One of the main health problems is the high prevalence of hypertension, along with the increasing number of new cases. The 2023 SKI results show a high prevalence of hypertension of 30.8% based on the results of checking blood pressure levels. The aim of this research is to find out how effective the two ARB antihypertensive drugs, namely Candesartan and Valsartan, are used at the Sultan Agung Islamic Hospital, Semarang. The population of this study were outpatient hypertensive patients who took the drugs Candesartan and Valsartan at the Sultan Agung Islamic Hospital, Semarang in the 2023 period. This study is an observational analysis conducted with a retrospective design. The purposive sampling technique produced 100 samples. Based on the results of the Man Whitney statistical test, there is no significant difference between the use of Candesartan and Valsartan in reducing blood pressure in outpatients at the Sultan Agung Islamic Hospital, Semarang. The conclusion of this research is that the p value is > 0.05.Key words: Hypertension, Effectiveness, Candesartan, Valsartan